Ubicación y dimensionamiento como parámetros en el diseño de almacenes: revisión del estado de arte - Hualpa Zúñiga, Andrés Mauricio; Suarez Roldan, Carolina (Ingeniería, 2013)
This article presents a survey of the literature concerning location and design as parameters in the design of stores. The survey includes identifi cation of models, methods, algorithms and tools that have been proposed to address this problem. The methodology applied was based on exploration, collection, classifi cation, evaluation and selection of the papers published in the period 1970-2012. The study concludes by identifying possible research routes in this area of interest according to the survey.